Transformada Z - Avelino, Simone Venturi (2016)
In this work the Z-transform is used to solve difference equations, aiming discrete mathematical models, with the main objective to develop a courseware in Portuguese, since most of the references are in English. The Z transformation approach has the following steps: definition of the unilateral Z-transform, existence condition, properties and inverse Z-transform, including demonstrations, examples and proposed exercises. The proposed material can be used to study discrete mathematics, by teachers and students in calculus classes for engineering courses, such as signal processing and sampled-data control systems; by High School teachers as a curiosity and further study of discrete math; and other related areas such as as Engineering, Economics and Computing.